Prion Protein Coding Gene (PRNP) Variability in Sheep from Turkey and Iran - Frootan, Fateme; Nikbakht, Gholamreza; Ozgenturk, Nehir Ozdemir; Un, Cemal (SPRINGER/PLENUM PUBLISHERS, 2012)
This study was designed to analyze variation of ovine prion protein in sheep breeds in Iran and Turkey. A competitive approach was used to analyze the open reading frame (ORF) of the ovine PRNP gene using a total of 186 samples from five indigenous sheep breeds. The ARQ allele was found to be the predominant allele in five breeds. The ARR allele was not observed in homozygous combination among the 11 genotypes found in the study. In addition, six other polymorphisms were indicated. These findings have great significance for estimating genetic variability in the PRNP gene with regard to Iranian and Turkish sheep. Since no information on the susceptibility of some genotypes identified in this study has been reported, no grouping was made on the basis of susceptibility.
Keywords: Gene variation; Prion gene; Iranian sheep; Turkish sheep; NATURAL SCRAPIE; PRP GENE; POLYMORPHISMS; SUSCEPTIBILITY; HEALTHY; ASSOCIATION; GENOTYPE; ALLELES; SUFFOLK; FLOCK; Biochemistry & Molecular Biology; Genetics & Heredity